Understanding Financial Behavior Among Gen Z: Evidence From Financial Literacy, Financial Inclusion, And Lifestyle in Denpasar, Indonesia - Tahu, Gregorius Paulus; Zakharia, Ido; Widnyana, I Wayan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Financial behavior is defined as the manner in which an individual administers and manages their financial resources. This encompasses a wide range of actions, including the management of expenses, the regulation of income, and the execution of financial decisions that are deemed to be the most suitable. Advancements in financial technology have precipitated substantial shifts in financial management patterns, particularly among Generation Z, who are progressively more accustomed to utilizing digital financial services for transactions and acquiring financial information. This observation suggests that Gen Z's financial behavior is not yet fully established and continues to be influenced by a variety of internal and external factors. This phenomenon provides a foundational framework for investigating the factors that shape Gen Z's financial behavior, with particular attention to the distinction between positive and negative financial behaviors. The objective of this study is to analyze the influence of financial literacy, financial inclusion, and lifestyle on Gen Z's financial behavior. The present study employs a quantitative approach, with a sample size of 140 respondents selected via purposive sampling based on the formula by Hair et al. The results indicate that financial literacy, financial inclusion, and lifestyle each have a positive and significant influence on Gen Z's financial behavior. It is anticipated that these findings will serve as a foundation for Gen Z to cultivate more judicious financial management skills and as a point of reference for future researchers to develop studies by incorporating additional variables that may influence financial behavior.